FORAGES AMMONIATING TECHNOLOGY TO INCREASE SHEEP PERFORMANCES - Kardaya, Dede (Jurnal Pertanian, 2017)
Research action of society service project in implementing forages ammoniating technology in increasing sheep performances had been conducted in eight months at Desa Gede Pangrango Kecamatan Kadu Dampit Kabupaten Sukabumi. The project was aim to increase practical ability of sheep farmers in forages ammoniating technology, forages quality, and to anticipate forages supply problems in draft season. Methods to attain the project goal included: education, training, demonstrating, practicing, and feeding ammoniated forages. Afterward, the sheep fed ammoniated forages had been weight monthly for three months. Methods to measure attainment of this goal project included questionnaire based interviewing and field monitoring to sheep farmers, parameters to measure ammoniated forages quality based on physical characteristics of ammoniated forages, whereas sheep responses to ammoniated forages measured by palatability and a three-month live weight gain. Results of the research action concluded that sheep farmers accepted well to introduction of forages ammoniating technology and able to ammoniating forages by themselves. Ammoniated forages-molasses mixes with ratio of 1% urea and 1% molasses of dry basis forages increased live weight gain of sheep 0.87 – 1.44 kg/3 months and higher than the weight gain of sheep fed non-ammoniated forages. Feeding ammoniated forages-molasses mixes increased profitability of sheep farmers as high as 18% (Rp78,354.00) whereas feeding ammoniated cassava peel-molasses mixes generated profit up to 51.44% (Rp222,966.00) higher than feeding non-ammoniated forages. Supporting sheep supply and market assurances will maintain the continuity of feeding of ammoniated forages.